Engineered outer membrane vesicle is potent to elicit HPV16E7-specific cellular immunity in a mouse model of TC-1 graft tumor - Wang S (Dove Medical Press, 2017)
Shijie Wang,1–3,* Weiwei Huang,1–3,* Kui Li,1–3 Yufeng Yao,1–3 Xu Yang,1–3 Hongmei Bai,1–3 Wenjia Sun,1–3 Cunbao Liu,1–3 Yanbing Ma1–3 1Laboratory of Molecular Immunology, Institute of Medical Biology, Chinese Academy of Medical Sciences & Peking Union Medical College, 2Yunnan Key Laboratory of Vaccine Research & Development on Severe Infectious Diseases, 3Yunnan Engineering Research Center of Vaccine Research and Development on Severe Infectious Diseases, Kunming, People’s Republic of China *These authors contributed equally to this work Purpose: Currently, therapeutic tumor vaccines under development generally lack significant effects in human clinical trials. Exploring a powerful antigen delivery system is a potential approach to improve vaccine efficacy. We sought to explore engineered bacterial outer membrane vesicles (OMVs) as a new vaccine carrier for efficiently delivering tumor antigens and provoking robust antitumor immune responses.Materials and methods: First, the tumoral antigen human papillomavirus type 16 early protein E7 (HPV16E7) was presented on Escherichia coli-derived OMVs by genetic engineering methods, acquiring the recombinant OMV vaccine. Second, the ability of recombinant OMVs delivering their components and the model antigen green fluorescent protein to antigen-presenting cells was investigated in the macrophage Raw264.7 cells and in bone marrow-derived dendritic cells in vitro. Third, it was evaluated in TC-1 graft tumor model in mice that the recombinant OMVs displaying HPV16E7 stimulated specific cellular immune response and intervened the growth of established tumor.Results: E. coli DH5α-derived OMVs could be taken up rapidly by dendritic cells, for which vesicle structure has been proven to be important. OMVs significantly stimulated the expression of dendritic cellmaturation markers CD80, CD86, CD83 and CD40. The HPV16E7 was successfully embedded in engineered OMVs through gene recombinant techniques. Subcutaneous immunization with the engineered OMVs induced E7 antigen-specific cellular immune responses, as shown by the increased numbers of interferon-gamma-expressing splenocytes by enzyme-linked immunospot assay and interferon-gamma-expressing CD4+ and CD8+ cells by flow cytometry analyses. Furthermore, the growth of grafted TC-1 tumors in mice was significantly suppressed by therapeutic vaccination. The recombinant E7 proteins presented by OMVs were more potent than those mixed with wild-type OMVs or administered alone for inducing specific cellular immunity and suppressing tumor growth.Conclusion: The results indicated that the nano-grade OMVs might be a useful vaccine platform for antigen delivery in cancer immunotherapy. Keywords: outer membrane vesicles, dendritic cells, HPV immunotherapy